Delimitation of the continental shelves in the Antarctic Treaty area: Lessons for regime, resource and environmental security - Weber, M (Routledge, 2012)
The resources of the Antarctic continental shelf region comprise oil, gas and diverse marine life. Important issues of both resource and environmental security are raised by the prospect of the exploitation of resources within the region yet to date, with the exception of fishing and limited marine bioprospecting, minimal attention has been paid to the commercial value of the continental shelves off Antarctica. In terms of resource and environmental security, the role of the Antarctic region may be influenced more by politics and regime dynamics than by economics. The acceptability of activities may change depending on the security of states' rights within the governing regime as well as depletion of resources elsewhere. The ability of the regime to accommodate resource and environmental security challenges provides evidence of the strength of that governing regime. A recent significant challenge to the Antarctic regime has been the issue of defining the outer limits of the continental shelves within the Antarctic Treaty area. This challenge stems from perceptions that defining the limits and exercising associated rights could contradict the Antarctic Treaty and the accepted norms with respect to the recognition (or otherwise) of sovereign claims over the continent. It could also be perceived as a precursor to mineral resource activities presently prohibited under the Protocol on Environmental Protection to the Antarctic Treaty (Madrid Prototcol). This chapter considers how the continental shelf delimitation process has enhanced resource, environmental and regime security within the Antarctic Treaty System (ATS). For the purposes of this chapter, the process of delimiting continental shelves south of 60S will be discussed. This includes the Antarctic continental shelf and those areas extending south from sub-Antarctic islands located north of 60S, such as the South Sandwich Islands and the Heard and McDonald Islands (HIMI). Although this process of elimination can potenially be seen as a threat to the governing regime, this chapter argues that the process has in fact enhanced regime security and provided further clarity concerning the development and protection of continental shelf resources. The cooperation exercised in this process between interested states indicates a willingness to promote longer term regime stability and security within the Antarctic region.